Efficacy Of Wood Vinegar Produced from Sengon and Jabon Wood Against on Schizophyllum commune - Kuswadi; Alkhadi; H. A. Oramahi; Slamet Rifanjani (Jurnal Biologi Tropis, 2023)
Wood dust waste can be used to make liquid smoke such as sengon wood and jabon wood. The aim of the research was to evaluate the antifungal properties of sengon and jabon wood liquid smoke in inhibiting the growth of the S. commune fungus in vitro. The process of making liquid smoke through the pyrolysis method. The research experiment was carried out using a factorial type randomized block design. The results showed that the type of liquid smoke and its concentration had a very significant effect on inhibiting the growth of the S. commune fungus. Fluid smoke from sengon and jabon wood actually restrained the development of S. commune by 100% at a concentration 2%. The conclusion is that the contents of liquid smoke from these two types of liquid smoke, namely total phenol and total acid, are compounds that function as antifungal agents.